VALDAHON - Centre du Village - Mabile | Raoul (Wikimedia Commons)
Carte postale ancienne issue de Wikimedia Commons. Titre: "VALDAHON - Centre du Village.". Horizontal, black and white postcard showing the town of Valdahon, France. The photograph was taken looking down the center of a street in the center of town. There are commercial buildings on both sides of the street, including the Hotel Roy in the background. Several pedestrians can be seen in the distance. A caption along the upper edge of the postcard reads: "Valdahon -- Centre du Village. Phot. Mabile Edit." The postcard is addressed to Miss M. O'Toole, 1912 Dodier St., St. Louis, Mo. It was written by Edward R. Dependahl to Mildred, his fiancee, while he was serving in France just after World War I. The postcard is dated December 27, 1918, and the handwritten note on the back reads: "ER Dependahl, U.S. Army, France, Soldiers Mail. Camp Valdahon, Fr. Dec. 27, 1918. Dearest Mil, Still in the same old place seeing and hearing the same old thing everyday. On the job and can't find time to keep up in my letters. Almost three weeks since I last heard from you. Love & x Ed." A stamp and signature indicate that the note passed the censors.
Droits : Licence No known copyright restrictions via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Carte postale